Monthly meetings of RDP: documenting the situation in ten village organizations in Matlab - Khan, Mahmuda Rahman (BRAC, 2019)
BRAC' s Rural Development Programme (RDP) holds monthly meeting of the VOs and fortnightly meetings of the Essential Health Care (EHC) Programme as a part of organizational development for the poor. This study aimed to understand and document the process of these meetings. More specifically, the study aimed to find out i) whether the issue-based meetings and the health forum were organized regularly; ii) what were the issues discussed; iii) how these issues were selected; iv) attendance in the meeting; v) level of participation of the members; vi) the behaviour and attitude of the person who conducted the meeting; and finally vii) the mode of the meeting whether participatory or lecture type. Only ten VOs from Matlab-RDP were selected for the study, five for issuebased meeting and five for health forum. Group discussion was conducted with each VO to get information about these meetings during the last six months, informar meeting with RDP staff were held to know BRAC's rules and policy regarding these meetings. Participant observation was also made to see the process of the meetings.